2013
DOI: 10.1073/pnas.1319832110
|View full text |Cite
|
Sign up to set email alerts
|

Crossing the divide between homogeneous and heterogeneous catalysis in water oxidation

Abstract: Enhancing the surface binding stability of chromophores, catalysts, and chromophore-catalyst assemblies attached to metal oxide surfaces is an important element in furthering the development of dye sensitized solar cells, photoelectrosynthesis cells, and interfacial molecular catalysis. Phosphonate-derivatized catalysts and molecular assemblies provide a basis for sustained water oxidation on these surfaces in acidic solution but are unstable toward hydrolysis and loss from surfaces as the pH is increased. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
154
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 136 publications
(160 citation statements)
references
References 53 publications
5
154
0
1
Order By: Relevance
“…ALD deposition of overlayers of TiO 2 or Al 2 O 3 has been shown to greatly enhance surface stability toward hydrolysis even in strongly basic solutions (25,26). We show here, for assembly 1 surface-bound to SnO 2 /TiO 2 , that ALD overlayers of TiO 2 or Al 2 O 3 provide both long-term stabilization on the oxide surface at pH 7 in a phosphate buffer, and, as a bonus, incrementally enhanced efficiencies for water splitting (23).…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…ALD deposition of overlayers of TiO 2 or Al 2 O 3 has been shown to greatly enhance surface stability toward hydrolysis even in strongly basic solutions (25,26). We show here, for assembly 1 surface-bound to SnO 2 /TiO 2 , that ALD overlayers of TiO 2 or Al 2 O 3 provide both long-term stabilization on the oxide surface at pH 7 in a phosphate buffer, and, as a bonus, incrementally enhanced efficiencies for water splitting (23).…”
mentioning
confidence: 71%
“…The latter is problematic because the rate of water oxidation is enhanced by added buffer bases, conditions that also enhance the rate of water oxidation (5,(17)(18)(19)(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%
“…Under our conditions, with electrochemical monitoring at pH 7.0, the observed behavior is similar to that observed earlier for related single-site Ru polypyridyl catalysts. For these catalysts, oxidation to Ru V =O is followed by rate-limiting O-atom transfer to H 2 O (11,16,17,19,20). Recently, Sun and coworkers (32) reported that the bdacarbene catalyst, [Ru III (bda)(mmi)(OH 2 )] (mmi is 1,3-dimethylimidazolium-2-ylidene) undergoes single-site catalytic water oxidation at pH 1.0. .…”
Section: Resultsmentioning
confidence: 99%
“…APT can promote dramatic rate enhancements. In a recent study on surface-bound [Ru(Mebimpy)(4,4′-((HO) 2 OPCH 2 ) 2 bpy)(OH 2 )] 2+ [4,4′-((HO) 2 OPCH 2 ) 2 bpy is 4,4′-bis-methlylenephosphonato-2,2′-bipyridine] stabilized by atomic layer deposition, a rate enhancement of ∼10 6 was observed with 0.012 M added PO 4 3− at pH 12 compared with oxidation at pH 1 (20).…”
mentioning
confidence: 99%
“…16 Furthermore, this approach generally involves less synthetic efforts, and it does not require the use of post-treatments based on advanced techniques (e.g., atomic layer deposition 17 ) or the deposition of polymeric overlayers 18 to further stabilize the linkage. On the other hand, the charge injection by these aggregates likely proceeds through π−π* exciton migration within the molecular assembly until achieving separation at the interface between the innermost molecular surface and the semiconductor.…”
Section: Introductionmentioning
confidence: 99%